Differentiation Learning Model for Students with Special Needs at UNIMA Manado - Dapa, Aldjon Nixon; Undap, Tiersa R. (Journal of ICSAR, 2023)
Differentiated learning is a learning approach process for students with different abilities in the same class. The purpose of differentiated learning is to maximize the growth/progress of each student and individual success through the adjustment of each student (from where he or she is), and assistance in the learning process. It is very urgent for students with special needs to be served according to their capacity.. From the research results obtained data, students with special needs at Unima consist of the blind, deaf, and physically disabled, without intellectual barriers, with diverse learning needs. With the act of making a difference in the media and learning models, they are able to master the lecture material well. Universities such as Manado State University, are able to implement it, and have an influence on the optimization and existence of inclusive learning services.